Belief in a Just World and Moral Personality as Mediating Roles Between Parenting Emotional Warmth and Internet Altruistic Behavior - Zhang, Ye; Chen, Liang; Xia, Yumeng (Frontiers in Psychology, 2021)
This study explores the influence of parental emotional warmth (PEW) on college students’ Internet altruistic behavior (IAB), and the mediating roles of personal belief in a just world (PBJW) and positive moral personality traits (PMPT). A total of 893 college students were assessed using questionnaires. Results: (1) PEW, PBJW, PMPT, and IAB are positively correlated with each other; (2) PEW can directly predict the IAB of college students; and (3) PEW can indirectly predict IAB through the mediating effect of PMPT and PBJW-PMPT. PBJW and PMPT account for 22.79% of the total influence of PEW on IAB.